The comprehensive and progressive agreement for the trans-pacific partnership: Data exclusivity and access to biologics - Zeleke Temesgen Boru (South Centre, 2020)
The test data rule concerning biological medicines (hereafter biologics) has been suspended from the scope of application of the Comprehensive and Progressive Agreement for the Trans-Pacific Partnership (CPTPP). While the suspension is commendable from the general standpoint of access to medicines and biologics in particular, the suspended provision may not provide assurance for the Parties to the CPTPP that they can rely on the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) flexibilities to promote access to biologics. In part this is because the Parties may end the suspension if and when they choose to do so. Simply put, the agreement does not promise that the suspended provision will remain suspended; rather, the Parties may revive the provision as originally negotiated under the Trans-Pacific Partnership (TPP) Agreement. The provision, if revived, may inhibit the Parties from implementing an obligation to ensure access to biologics, medicines that target chronic and rare ailments like cancer, clotting factors and several others. Against this backdrop, this research paper focuses on the test data rule relating to biologics as negotiated under the TPP. In particular, it explores whether the CPTPP Parties would be able to use TRIPS flexibilities effectively to promote access to biologics, as advanced by international human rights instruments, in particular the International Covenant on Economic, Social and Cultural Rights (ICESCR). The paper also provides potential responses to the question of whether the test data rule deters the realization of access to biologics. In response, the author has determined that the rule on test data can limit access to biologics, as it would delay the entry of affordable biologics (biosimilars) into markets.
Keywords: 300; Access to Medicines; Affordable Medicines; Biologics; Biosimilars; Biotherapeutics; Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP); Data Exclusivity; Health; Human Rights; Intellectual Property; International Covenant on Economic Social and Cultural Rights (ICESCR); Trans-Pacific Partnership (TPP); TRIPS; UNHLP on Access to Medicines; World Health Organization (WHO); World Intellectual Property Organization (WIPO); World Trade Organization (WTO)